Towards an understanding of the lipophilicity of non-coded amino acids: computational simulations of proline analogs - Matamoros Parker, Paulina De Los Angeles (2022)
Amino acids are the backbone for the formation of biopolymers known as proteins. One of them, proline, can be found in high concentrations in collagen, being this protein the most supportive for the skin, tendons, bones, and connective tissue, promoting their health and recovery. Here, we compute the lipophilicity of 25 non-coded proline analogs using the quantum mechanics implicit solvation model SMD. Comparison with the experimental data provided for partition coefficients yielded a root-mean square error (rmse) of 0.72 (log P units). Overall, the results support the appropriateness of SMD solvation model for computing the n-octanol/water partition coefficient in proline analogs, which can be used to tune the hydrophobic properties of bioinspired synthetic peptides.